Penanaman Nilai Moral dan Agama Pada Anak di RA An-Nuriyah - Faila Sufa (AL-BURHAN, 2023)
The objectives of this study were (1) to describe the cultivation of Islamic morals and religion in kindergarten children by teachers in RA An-Nuriyah, (2) to describe the form of curriculum, learning methods, and media used by teachers in instilling moral and religious values in kindergarten children by teacher at RA An-Nuriyah, (3) Describe what factors encourage and hinder the inculcation of moral and religious values in kindergarten children by teachers in RA An-Nuriyah. The research design used is a qualitative approach. Sources of research data are teachers and children as well as documents used such as RPPM and RPPH. Data collection methods are observation, interview, and documentation. The results showed that the cultivation of Islamic moral and religious values in RA An-Nuriyah regarding the teaching of faith, morality, worship, and memorization of the Al-Qur'an was less varied. The curriculum still uses KTSP, while the learning methods and media used in RA An-Nuriyah are less varied. The driving factors for the cultivation of moral and religious values are children's motivation, family environment, school environment, and community environment, while the inhibiting factors are family environment, school environment and community environment. It is recommended that teachers improve the learning methods and media used in teaching moral and religious values to kindergarten children.